Correction to: Appearance of a population of the mangrove rail Rallus longirostris (Rallidae) in salt marshes invaded by the exotic tanner grass Urochloa arrecta (Poaceae) and its disappearance after plant management - Bornschein, Marcos R. [UNESP]; Teixeira, Larissa [UNESP]; de Morais Guerra, Bruno [UNESP]; Melchiori, Bianca L. [UNESP]; Reinert, Bianca L. [UNESP]; Sandretti-Silva, Giovanna [UNESP] (Springer Nature, 2023)
The captions of the following figures were inadvertently placed incorrectly. Please find the details below on how to read the captions correctly: The correct caption of the first image (Fig. 1...) can be found after Fig. 2.... The correct caption of the second image (Fig. 2...) can be found after Fig. 3.... The correct caption of the third image (Fig. 3...) can be found after Fig. 1.... Springer wishes to apologize for any inconvenience caused.
Correction to: Appearance of a population of the mangrove rail Rallus longirostris (Rallidae) in salt marshes invaded by the exotic tanner grass Urochloa arrecta (Poaceae) and its disappearance after plant management (Wetlands, (2022), 42, 8, (124), 10.1007/s13157-022-01642-7)